Spiritual leadership values and organisational behaviour in Malaysian private institutions of higher education - Wong, Shiet Ching *; Malissa Maria Mahmud, *; Omar, F. (Universiti Putra Malaysia Press, 2015)
Malaysia wants to be a part of the bandwagon in the industry of higher education, thus, the number of private higher education institutions has grown drastically in the recent years. Moreover, the assimilation of cultures and values among the races in Malaysia has contributed distinctive organisational cultures that affect leadership values and organisational behaviour specifically in the private institutions of higher education sector. The purpose of this study is to identify spiritual leadership values embraced by the leaders in private institutions of higher education, as well as the relationship between spiritual leadership values and organisational behaviour (job satisfaction, organizational commitment and intention to quit). In total, 302 academics and administrative staff from 7 private institutions of higher education in Malaysia participated in the study. Questionnaire and non-probability sampling were used in the data collection for this study. The findings show that love, hope, and peace are associated with membership and meaning, meanwhile membership and meaning are associated with organisational behaviour. Hence, this study has contributed in leadership training that will affect the turnover rate and ultimately result a cost effective managerial policing in the Malaysian private institutions of higher education.